Numerical Simulation of Cavitation Bubble Growth within a Droplet. (15th July 2015) - Lü, M.; Ning, Z.; Yan, K.; Fu, J.; Sun, C.-H.
Abstract : Cavitation bubbles, which always exist in the diesel jet leaving the nozzle and in diesel droplets breaking up from the jet as a result of supercavitation of the diesel within the injection nozzle, increase the instability of jet and droplets in part due to the two-phase mixture, while the mechanism of this effect is still unclear. Cavitation bubble expansion within the diesel droplet has been simulated numerically based on the volume of fluid (VOF) method, and the control mechanism of bubble growth process is analyzed by Rayleigh-Plesset equation. The process of bubble growth is divided into three parts, including surface tension controlled domain, comprehensive competition controlled domain and inertial force controlled domain. During the first stage, cavitation bubble growth is controlled by the surface tension, and the decrease of the surface tension leads to the increase of the bubble growth rate. During the second stage, the bubble growth rate is controlled by the comprehensive competition of the surface tension, the inertial force and the viscous force. During the third stage, the process of bubble growth is majorly controlled by the inertial force.